Effect of Endurance and Breathing Training Versus Circuit and Breathing Training On Blood Pressure in Prehypertensive Overweight Adults: Life Sciences-Physiotherapy - Saraswathi, K.; Nandhagopal, Koushik Kumar; Rajalakshmi, G.; Thirulogachandar, G.; Muthulakshmi, K.; Revathi, P.; Aishwarya, B. (International Journal of Life Science and Pharma Research, 2023)
Hypertension is one among the leading risk factor for mortality and it is called as “the silent killer”. The new creation of the term ‘prehypertension’ classification by the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure JNC 7 guidelines has provided a new path to the researchers to examine this group separately as it decreases the average life expectancy by as much as five years. Physical activity in the form of regular aerobic exercise has been proven in prevention of high blood pressure as well as the lowering of blood pressure among all levels of hypertension. The circuit training and endurance training exercises are known to reduces both systolic and diastolic arterial blood pressure along with improvement of health related quality of life. Breathing training exercises is the only simple method to improve respiratory control to reduce the blood pressure in prehypertensive individuals. The aim of this study is to examine the effects of endurance and breathing training versus circuit and breathing training on blood pressure, body mass index, waist circumference and quality of life in pre hypertensive overweight adults. This is an experimental design with pre and post comparative study. The subjects of 25-40 years of overweight both male and female, clinically diagnosed with prehypertension were included in the study. Those with known cardiac, pulmonary, neurological and musculoskeletal disorders were excluded in the study.40 subjects were randomly assigned into two groups, Group A received endurance training with breathing exercise while Group B received circuit training and breathing exercise for 12 weeks and 5 sessions per week. The outcome measures were blood pressure, BMI, waist circumference and quality of life. The outcome tools were sphygmomanometer, weighing machine, Stadiometer, inch tape and SF 36 Short-Form 36 Questionnaire. On comparing Pre-test and Post-test within Group A and Group B on blood pressure, body mass index, waist circumference and quality of life shows a significant difference in mean values at P<0.001. Thus this study concludes that 12 weeks of circuit training and breathing exercise reduces blood pressure, body mass index, waist circumference and improves the quality of life in pre hypertensive overweight adults.